Analisis Hirarki Proses Pengelolaan Zakat Produktif di Kota BAZNAS Kota Cirebon - Suci Widiastuti, Dwi; Sekar Arum Sari, Dila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Zakat for Muslims, especially in Indonesia and even in the Islamic World in general, has been explained as an important part of the perfection of Islamic teachings.The research uses descriptive quantitative methods with data collection techniques through interviews, observations, documentation.This study used a questionnaire from selected informants consisting of 7 respondents who are experts in Zakat Management. The data obtained isthen analyzed using Analytical Hierarchy Processes (AHP) with the help of Excel.The results of this study are Zakat Management influenced by 3 faktor main programs that are ranked first are Applications (64), second regulation (23), and the last rank of HR (13).